Pemasaran Online Keripik Singkong Pada Masa Pandemi Covid-19 Di Desa Kendalpayak Kecamatan Pakisaji Kabupaten Malang - Riril Mardiana Firdaus; Roni Alim Ba’diya Kusufa; Dianawati Suryaningtyas (Jurnal ABM Mengabdi, 2022)
Small and medium business groups have a very strategic role in improving the economy and people's welfare. The role of SMEs is very important in marketing activities to support household income. Until now, the development of the chip business has been mostly carried out by the people of Kendalpayak Village, Pakisaji District, Malang Regency. Along with the intense competition in the business world, only a few people have been able to survive until now. Only people who have motivation and tenacity in business can come out victorious. In Kendalpayak village, there are two chips business group partners that still exist today. Among them are: (1) Partners of the “Cassava Chips Key Cap” business group, whose owner is Mr. Misbachul Munir, 37 years old. He has been starting this cassava chip business for 2 years, and is assisted by 4 employees. Keycap cassava chips only produce 1 original flavor, and have not produced any flavored chips yet. In business activities, marketing becomes the spearhead. Marketing will determine whether the business being run can survive and generate profits or suffer losses. Production and marketing have a very close relationship. Production will not increase if it is not supported by a good marketing system. In the face of economic uncertainty and home-based businesses, it is necessary to formulate an appropriate marketing strategy to develop the business. The methods offered are: (a) training and mentoring as well as providing a special room for opening chips (b) training and mentoring as well as procuring proper plastic packaging equipment (c) training and marketing assistance through online media, (d) financial management training and assistance through a computerized system.